2007
DOI: 10.1152/ajpregu.00880.2006
|View full text |Cite
|
Sign up to set email alerts
|

Development of contractile dysfunction in rat heart failure: hierarchy of cellular events

Abstract: The cellular mechanisms underlying the development of congestive heart failure (HF) are not well understood. Accordingly, we studied myocardial function in isolated right ventricular trabeculae from rats in which HF was induced by left ventricular myocardial infarction (MI). Both early-stage (12 wk post-MI; E-pMI) and late, end-stage HF (28 wk post-Mi; L-pMI) were studied. HF was associated with decreased sarcoplasmic reticulum Ca2+ ATPase protein levels (28% E-pMI; 52% L-pMI). HF affected neither sodium/calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 46 publications
7
30
0
1
Order By: Relevance
“…Because of the high amount of detergent used in the homogenization buffer, it is unlikely that much of the PKC remained in the particulate (myofilament) fraction, and thus the amount of PKC protein in the detergent extracted fraction represents most of the PKC found inside the ventricular myocyte. At an early stage of HF, characterized by preserved myofilament function, 25 we found no changes in PKC-␣ expression or activation ( Figure 1A and 1B). In contrast, PKC-␣ expression was increased Ϸ4-fold in CHF relative to age-matched control ventricles ( Figure 1C).…”
Section: Pkc-␣ Isozyme Expression In Experimental Early Hf and End-stmentioning
confidence: 78%
See 2 more Smart Citations
“…Because of the high amount of detergent used in the homogenization buffer, it is unlikely that much of the PKC remained in the particulate (myofilament) fraction, and thus the amount of PKC protein in the detergent extracted fraction represents most of the PKC found inside the ventricular myocyte. At an early stage of HF, characterized by preserved myofilament function, 25 we found no changes in PKC-␣ expression or activation ( Figure 1A and 1B). In contrast, PKC-␣ expression was increased Ϸ4-fold in CHF relative to age-matched control ventricles ( Figure 1C).…”
Section: Pkc-␣ Isozyme Expression In Experimental Early Hf and End-stmentioning
confidence: 78%
“…Ascending aortic banding and myocardial infarction (MI) were performed on 4-week female Sprague-Dawley rats as described previously, with slight modifications. 11,15 Animals in the early HF cohort were followed for a period of 12 weeks, 25 whereas animals in the end-stage CHF group were followed for 32 to 36 weeks until they transitioned to end-stage CHF. Unoperated age-matched animals served as controls.…”
Section: Animal Models Of Ventricular Hypertrophy and Chfmentioning
confidence: 99%
See 1 more Smart Citation
“…There is controversy regarding the effects on EC 50 in heart failure, with reports of decreased EC 50 (increased myofilament Ca 2ϩ sensitivity) in heart failure in some, but not all, studies (3,7,12,17,21,30). We found that the effects of heart failure on EC 50 depended on the experimental context.…”
Section: Discussionmentioning
confidence: 68%
“…Both of these indexes of cardiac muscle contractility (PRSW and dP/dt max vs. EDV max ), demonstrated a sex-related difference in 10 wk post-MI mice during the decompensation to failure. Despite the activation of neurohormonal compensatory mechanisms, myocyte contractility is depressed in the infarcted heart, partly due to dysregulation of excitation-contraction (E-C) coupling (8,15,19). The expression of key proteins and the signaling components involved in E-C coupling regulation differ between females and males and are associated with slight functional differences (6).…”
Section: Discussionmentioning
confidence: 99%